2005
DOI: 10.1097/01.psy.0000174994.91245.34
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the Serotonin (5-HT)-2 Receptor and Insulin Sensitivity: Implications for Atypical Antipsychotics

Abstract: The selective 5-HT2 antagonist ketanserin impaired insulin sensitivity. This effect was possibly mediated by suppression of 5-HT(2A) receptor mediated glucose uptake in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…5). These findings may well help explain the contradictory discoveries about why ketanserin impairs insulin sensitivity, yet sarpogrelate improves the insulin sensitivity and glucose metabolism (Takishita et al, 2004;Gilles et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…5). These findings may well help explain the contradictory discoveries about why ketanserin impairs insulin sensitivity, yet sarpogrelate improves the insulin sensitivity and glucose metabolism (Takishita et al, 2004;Gilles et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…Work in healthy volunteers has since shown that 5-HT 2 antagonists can significantly decrease insulin sensitivity compared with placebo (P = 0.047), an effect possibly mediated by the suppression of 5-HT 2A receptor-mediated glucose uptake in skeletal muscle. 86 It should be noted, however, that most atypical antipsychotics have stronger antagonistic effects at 5-HT 2A and 5-HT 2C than at 5-HT 1A , 85 and that 5-HT 2C antagonism is most closely correlated with an increased risk of diabetes and weight gain. 53 Consistent with this notion, 5-HT 2C knockout mice develop insulin resistance and impaired glucose tolerance and experience severe weight gain.…”
Section: Diabetes 62mentioning
confidence: 99%
“…Paroxetine increased serum 5-HT levels through inhibiting the reuptake of 5-HT by these cells. Several reports have demonstrated that 5-HT affects insulin secretion via 5-HT receptors [30,42,43] . Our study showed that unlike intracellular 5-HT, extracellular 5-HT inhibited rather than stimulated insulin secretion, which was in an agreement with previous reports [37] .…”
Section: Discussionmentioning
confidence: 99%